Procesamiento y Caracterización de Titanio Poroso Pulvimetalúrgico para Implantes y Prótesis Articulares (2011)
ABSTRACT: Commercially pure titanium (c.p. Ti) is one of the best metallic biomaterials for bone tissue replacement. However, one of its main drawbacks, which compromise the service reliability of the implants, is the stress shielding phenomenon (Young's modulus mismatch with respect to that one of the bone) and there are several previous works trying to solve this problem. One of the alternatives more studied to solve that problem has been the development of biocomposites implants and, more recently, fabrication of titanium porous implants. In this work, porous samples of c.p. Ti Grade 4 were obtained using conventional powder metallurgy technique and the influence of the processing parameters (compacting pressure and sintering temperature) in the microstructure features (size, type, morphology and percentage of porosity) as well as in mechanical properties (compressive yield strength and conventional Young's modulus) were investigated. The results indicated that there is an increment in density, roundness of pores and mean free path between them, as compacting pressure and/or sintering temperature is increased. The Young's modulus and yield strength showed the same behavior. The better stiffness results, in the central part of cylindrical samples, were obtained for a uniaxial compression of 38.5 MPa, using a sintering temperature of 1000 and 1100ºC. Evaluation of porosity and Young's modulus along a cylindrical sample divided in three parts, showed that is possible to obtain a titanium sample with graded porosity which could be used to design implants. This approach opens a new alternative to solve the bone resorption problems associated to stress shielding phenomenon